Effect of Au ion beam on structural, surface, optical and electrical properties of ZnO thin films prepared by RF sputtering. Issue 14 (1st October 2018) - Fiaz Khan, M.; Siraj, K.; Sattar, A.; Majeed, S.; Faiz, H.; Khan, M.I.; Raisanen, J.; Mizohata, K.; Kemell, M.
Abstract: In the present work, ZnO thin films were irradiated with 700 keV Au + ions at different fluence (1 × 10 13, 1 × 10 14, 2 × 10 14 and 5 × 10 14 ions/cm 2 ). The structural, morphological, optical and electrical properties of pristine and irradiated ZnO thin films were characterized by X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), scanning electron microscope (SEM), spectroscopy ellipsometry (SE) and four point probe technique respectively. XRD results showed that the crystallite size decreased from pristine value at the fluence 1 × 10 13 ions/cm 2, with further increase of ion fluence the crystallite size also increased due to which the crystallinity of thin films improved. SEM micrographs showed acicular structures appeared on the ZnO thin film surface at high fluence of 5 × 10 14 ions/cm 2 . FTIR showed absorption band splitting due to the growth of ZnO nanostructures. The optical study revealed that the optical band gap of ZnO thin films changed from 3.08 eV (pristine) to 2.94 eV at the high fluence (5 × 10 14 ions/cm 2 ). The electrical resistivity of ZnO thin film decreases with increasing ion fluence. All the results can be attributed to localized heating effect by ions irradiation of thin films and well correlated with each other.